Reconstruction of Ultrahigh‐Aspect‐Ratio Crystalline Bismuth–Organic Hybrid Nanobelts for Selective Electrocatalytic CO2 Reduction to Formate. (8th May 2022) - Zeng, Guang; He, Yingchun; Ma, Dong‐Dong; Luo, Shiwen; Zhou, Shenghua; Cao, Changsheng; Li, Xiaofang; Wu, Xin‐Tao; Liao, Hong‐Gang; Zhu, Qi‐Long
Abstract: The morphology and active site engineering of electrocatalysts is an efficient strategy to improve the intrinsic activity and selectivity of electrocatalytic CO2 reduction. Here the ultralong and thin Bi nanobelts (Bi‐NBs) are fabricated, which feature a high edge‐to‐facet ratio and high‐degree connectivity is inherited from the ultrahigh‐aspect‐ratio crystalline bismuth−organic hybrid nanobelts, through a cathodically in situ reconstruction process. The unique nanostructure of Bi‐NBs leads to a significantly enhanced performance for electrocatalytic CO2 reduction with a near‐unity formate selectivity and high formate partial current density, which is far superior to those of the discrete Bi counterparts with low edge‐to‐facet ratios. Notably, Bi‐NBs perform ultrahigh formate selectivity over a broad potential window with a high current density reaching 400 mA cm −2 for formate production in a flow cell. Moreover, it is ultrastable to continuous electrolysis for nearly 23 h at 200 mA cm −2 without compromising the selectivity. Based on calculations, the enhanced performance is closely related to the high edge‐to‐facet ratio of Bi‐NBs, since the rich edge sites are conducive to the stabilization of the key *OCHO intermediate for formate production. In addition, the ultralong and interconnected Bi‐NBs provide "expressways" for electron transfer during CO2 electroreduction, further contributing to the improved performance. Abstract : Thin Bi nanobelts inheriting the high edge‐to‐facet ratio and high‐degree connectivity are fabricated by cathodical in situ conversion of bismuth–organic hybrid nanobelts. Such distinctive structure is conducive to stabilization of the key *OCHO intermediate for formate production and acts as "expressways" for electron transfer leading to an excellent electrocatalytic performance toward electrocatalytic CO2 reduction to formate.